Synthesize of Emulsion Polymer Latex for Sub-Grade CBR Improvement in The Road Construction - Moto, Keba; Julian, V.; Syamsudin, Syamsudin; Wiradi, T. A.; Wijaya, S. R. (UI Scholars Hub, 2004)
Synthesize of emulsion polymer latex for sub-grade CBR improvement in the road construction. Latex polymer for California Bearing Ratio (CBR) enhancement in sub-grade soil of road building has been prepared by emulsion polymerizations technique. The prepared polymer then characterize by Fourier Transform Infrared (FTIR). For application purpose, CBR test was done to the compacted polymer added-soil. The CBR test is done also for both soaked and unsoaked samples. It is found that our latex polymer is better then other imported latex polymer. For the latex polymer, which is design to have Temperatur glass (Tg) around 9.8-19.6o, indicating the formation of C=O and – C-O-C- bonds at 1732-1736 cm-1 energy absorption as binder groups. CBR test results show that our latex polymer has CBR value around 15-18 % compare to the soil without polymer binder.